Analisis Self Efficacy dan Anxiety Pada Kesuksesan Adopsi Mobile Wallet dengan Model UTAUT - Meilinda Dwi Anugrah; Hermaya Ompusunggu (LPPM Universitas Putera Batam, 2020)
This study aims to identify what factors influence an individual's intention to use a mobile wallet (m-wallet) with the UTAUT (Unified Theory of Acceptance and Use of Technology) model. This study examines which variables in the UTAUT model affect the user's intention to use a mobile wallet as a digital payment. This research is a quantitative study using primary data. Data collection techniques and research instruments are distributed directly to m-wallet application users in Batam City online. The total number of questionnaires distributed was 200 questionnaires. However, only 100 respondents can be used sample of study, while the rest cannot be used in the sample because they have never used m-wallet and are not domiciled in the Batam area. The data analysis technique used the validity test and the reliability test. The validity test uses the Average Variance Extracted (AVE) value, if the AVE value is> 0.5, the research instrument is declared valid. While the reliability test was carried out using Cronbach's alpha value, if the alpha value was> 0.6, then the instrument was declared reliable. Researchers used partial least square (PLS) as a method of statistical analysis. From 100 respondents, it was found that self-efficacy did not have a direct effect on the intention to use m-wallet, while anxiety had no effect and showed a positive direction on the intention to use m-wallet and social influence had a positive effect on the intention to use m-wallet.